Factors related to childbearing intentions among women: a cross-sectional study in health centers, Saveh, Iran - Marzieh Araban; Mahmood Karimy; Bahram Armoon; Fereshteh Zamani-Alavijeh (SpringerOpen, 2020)
Abstract Background One of the most important demographic challenges over the recent three decades in the world has been a significant fall in the fertility rate. This study aimed to investigate factors related to childbearing intentions among a sample of Iranian women. Methods A cross-sectional study of a sample of Iranian married women attending 8 centers in Saveh was conducted in 2015. A total of 483 married women 15-49 years old participated in this study. A questionnaire was used to collect data about demographics, attitude, subjective norms, marital satisfaction, social support, hopefulness, and behavioral intentions of childbearing. Results Overall, 62% of women in the study intended to have children in the next 2 years. The group willing to have children had a higher score on attitude, subjective norms, hopefulness, perceived social support, and marital satisfaction compared to the group unwilling to have children. Also, the regression results revealed that the variables of age, literacy status, employment status, husband literacy, women and husband occupation status, attitude, subjective norms, hopefulness, perceived social support, and marital satisfaction were significant predicting factors for childbearing intention (P < 0.05). Conclusions and recommendations The findings highlighted the importance of psychological factors such as marital satisfaction and social support in the childbearing process. Thus, health system planners should pay more attention to these determinants of fertility intention.